Penerapan Pola Pengajaran Bahasa dan Sastra Daerah Bali sebagai Penguatan Kecerdasan Afektif, Kognitif dan Psikomotorik Peserta Didik - Ni Nyoman Perni (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Application of pattern language teaching and literature area of Bali is seen very important applied in of all potential and existing intelligence in learners. As it known, that every participant has a range of student potential and intelligence who strived to be developed early on so that they can grow and develop optimally. As Bloom's taxonomy refers to, that there are three aspects that should be in students in learning, i.e. aspects of apectif-related behavior, cognitive-related knowledge, intellect and related psychomotor skills. So, these three aspects that influence the development of maximum mental attitude, behavior and abilities of learners, so that the purpose of education can be achieved. Pattern language learning and literature area of Bali is pattern learning based on the application of language and literature area of Bali as the local value and charge implemented in learning. The pattern became a cornerstone of learning with student-centered approach as learners and teachers as educators.